Patients' Convergence of Mass and Interpersonal Communication on an Online Forum: Hybrid Methods Analysis - Sanders, Remco; Araujo, Theo B; Vliegenthart, Rens; van Eenbergen, Mies C; van Weert, Julia C M; Linn, Annemiek J (JMIR Publications, 2020)
BackgroundPatients are increasingly taking an active role in their health. In doing so, they combine both mass and interpersonal media to gratify their cognitive and affective needs (ie, convergence). Owing to methodological challenges when studying convergence, a detailed view of how patients are using different types of media for needs fulfillment is lacking. ObjectiveThe aim of this study was to obtain insight into the frequency of reported convergence, how convergence affects what posters write online, motives for posting, and the needs posters are trying to fulfill. MethodsUsing a hybrid method of content analysis and supervised machine learning, this study used naturally available data to fill this research gap. We analyzed opening posts (N=1708) of an online forum targeting cancer patients and their relatives (Kanker.nl). ResultsNearly one-third of the forum opening posts contained signs of convergence in mass or interpersonal media. Posts containing mass media references disclosed less personal information and were more geared toward community enhancement and sharing experiences compared to posts without convergence. Furthermore, compared to posts without signs of convergence, posts that included interpersonal media references disclosed more personal information, and posters were more likely to ask for the experiences of fellow users to fulfill their needs. Within posts containing signs of convergence, posts including interpersonal media references reported fewer shortages of information, disclosed more information about the disease, and were more active in seeking other posters' experiences compared to posts containing mass media references. ConclusionsThe current study highlights the intertwining of media platforms for patients. The insights of this study can be used to adapt the health care system toward a new type of health information-seeking behavior in which one medium is not trusted to fulfill all needs. Instead, providers should incorporate the intertwinement of sources by providing patients with reliable websites and forums through which they can fulfill their needs.